2017
DOI: 10.1002/cne.24201
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and central anatomical organization of cutaneous afferent subtypes in a rat nociceptive intersegmental spinal reflex

Abstract: Stimulation of rat segmental dorsal cutaneous nerves (DCNs) evokes the nociceptive intersegmental cutaneus trunci muscle (CTM) reflex. The reflex consists of early and late responses, mediated by Aδ and C fibers, respectively, based on required stimulation strengths, and shows segmental differences in terms of amplitude and duration. We have now investigated whether the peripheral or central anatomy of nociceptive afferent subtypes in different DCNs also vary in a segmental manner. The numbers of different axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(47 citation statements)
references
References 72 publications
(196 reference statements)
7
40
0
Order By: Relevance
“…Anti‐CTB is a polyclonal antibody raised in goats against purified CTB from Vibrio cholerae type Inaba 569B, which was obtained from List Biological Laboratories (Cat# 703, RRID:AB_10013220). Using this antibody in the present study, we detected CTB‐labeled afferents distributed in lamina III–IV, as was reported previously (Florence et al, ; Lee, White, Chung, & Tansey, ; Maslany et al, ).…”
Section: Methodssupporting
confidence: 84%
“…Anti‐CTB is a polyclonal antibody raised in goats against purified CTB from Vibrio cholerae type Inaba 569B, which was obtained from List Biological Laboratories (Cat# 703, RRID:AB_10013220). Using this antibody in the present study, we detected CTB‐labeled afferents distributed in lamina III–IV, as was reported previously (Florence et al, ; Lee, White, Chung, & Tansey, ; Maslany et al, ).…”
Section: Methodssupporting
confidence: 84%
“…The anti‐CTB antibody is a commercial polyclonal antibody (List Biological Laboratories) raised in goats against the purified CTB from Vibrio cholerae type Inaba 569B. We observed CTB‐labeled afferents detected by this antibody being distributed in lamina (L) III to LIV, as previously reported (Florence, Wall, & Kaas, ; Lee, White, Chung, & Tansey, ; Maslany, Crockett, & Egger, ).…”
Section: Methodssupporting
confidence: 86%
“…The anti‐CTB antibody (#703; List Biological Laboratories) produced in goats with CTB (choleragenoid) has been frequently used to label injected CTB as a retrograde tracer. This tracing and detection method has been successfully applied in numerous previous studies (for example, Rosin, Chang, & Guyenet, ; Lee, White, Chung, & Tensey, ). Preabsorption of the antibodies from antiserum with excessive CTB molecules showed no labeling whereas adjacent tissue sections showed typical CTB labeling without preabsorbing the antibodies (Rosin et al, ).…”
Section: Methodsmentioning
confidence: 99%